(untitled) (Revista Argentina de Musicología, 2018)
As a consequence of the processes of globalisation and massification, there is u trend in progress for the limits that set Argentine rock-and-roll apart frorn other musical manifestations to fade out. However, it was and still is decidedly emblematic and stigmatising. It has always tried to model and to put forward an identity: has always built limits. A possible way to inquire about this apparent paradox is to try to apprehend, not the precise boundary between rock and non rock musics, musicians, audiencies, and rock.ing altitudes, but the interplay that resides in going beyond the boundary to acquire two central qualities peculiar to all rock rnus icians: transgression and innovation, something that requires staying out a short enough time so as not to lose one’s soc iocultural identity. In an attempt to take sorne steps in this direction, we will talk about a feature of rock’n roll in Argentina, and surely in rnost countries where rock has developed. This distinctive quality consists in deconstructing through its defiant ideology, the musical, visual and political limits imposed by its own history, allowing access to the alien and the different. In turn, these incorporations generate dissidences necessary for the reproduction of the sociocultural formation, since disagreement constitutes a vital aspect of its existence.